Grounding Staff Development for Networked Learning Environments - McAteer, Erica; Littlejohn, Alison; Peacock, Susi; Juwah, Charles; Bates, Dennis; Bruce, Stephen (Proceedings of the International Conference on Networked Learning, 2002)
The presentation to the Networked Learning Conference session participants will describe some of the research, development and practice experience that underpinned the ScotCIT* ELICIT materials development, funded by the Scottish Higher Education Funding Council (SHEFC) the rationale for its use in that development, and outcomes of expert practitioner review of some of the materials for networked learning contexts. It will also take forward models of development for flexible on-line courses which can adapt to a variety of contexts, customisable by the user communities concerned. This paper backgrounds the conference presentation, supporting what we hope will be a framework for discussion and development with participants at the session. Its perspective is very much that of its first author, but with agreement and support from the other members of the project team. All of us feel that we should share the ‘ELICIT’ experience with the wider community as we work on future re-purposing and wider implementation of the resources.